The KNAT3a1-WND2A/3A module positively regulates fiber secondary cell wall biosynthesis in Populus tomentosa - Kuan Sun; Di Fan; Yingying Peng; Chang Liu; Lingfei Kong; Ting Lan; Xianqiang Wang; Dan Li; Chaofeng Li; Keming Luo (Horticultural Plant Journal)
The secondary cell wall (SCW) is essential for plant growth and development in vascular plants, and its biosynthesis is mainly controlled by a complex hierarchical regulatory network involving multiple transcription factors (TFs) at the transcription level. However, TFs that specifically regulate secondary xylem have not been widely reported. In this study, we described a poplar KNOTTED1-like homeobox (KNOX) TF PtoKNAT3a1, which was mainly expressed in the expanding xylem cells of stems. PtoKNAT3a1 overexpression caused fiber SCW thickening and increased all measured SCW compositions by upregulating the expression of SCW -biosynthetic genes and -associated TFs, but had no effect on the vessels of SCW. The opposite phenotype was observed in the PtoKNAT3a1-knockout lines. Hence, we further demonstrated that PtoKNAT3a1 could physically interact with the NAC master switches PtoWND2A/3A to enhance the expression of downstream MYB TFs and SCW biosynthetic genes (including PtoMYB20, PtoMYB21, PtoMYB90, PtoCoMT2, PtoGT43B and PtoCesA8). Meanwhile, the studies also demonstrate that the KNAT3 has functional differentiation in xylem development. Taken together, these data suggest that the KNAT3a1-WND2A/3A module positively regulates fiber development of the secondary xylem in poplar via the WND2A/3A-mediated hierarchical regulatory network, and supplies useful information for fiber SCW formation. The research not only deepens the understanding of the hierarchical regulatory network affecting SCW formation but also supplies genetic resources and molecular targets for plant fiber utilization.